Recycled aggregate hydraulic roller compacted concrete and preparation method thereof
By modifying the recycled aggregate micro powder and adding modified rubber powder and copper ore sand, the concrete mix ratio is optimized, and the problem of poor anti-freeze, anti-seepage and temperature conduction performance in recycled aggregate hydraulic rolling concrete is solved. , achieve performance improvement and temperature crack control.
Patent Information
- Application Number
- CN202510048435.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When regenerated aggregates are used in hydraulic rolling concrete, poor frost resistance, impermeability and poor temperature conduction performance make it difficult to control temperature cracks.
By modifying the regenerated aggregate micro powder and replacing part of the blend, adding modified rubber powder and copper ore sand, and scientifically optimizing the concrete mix ratio to improve the various properties of concrete.
The recycled aggregate hydraulic roller concrete has been improved in the frost resistance, seepage resistance and temperature conduction performance, effectively reducing the occurrence of temperature cracks, and meeting the technical requirements of dam-building materials in water conservancy and hydropower projects.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydraulic rolled concrete, and in particular relates to recycled aggregate hydraulic rolled concrete, and also relates to a preparation method of the recycled aggregate hydraulic rolled concrete. Background Art
[0002] At present, there are many studies on ordinary concrete with recycled aggregate in China. Its mix design, concrete performance and application technology have become relatively mature. However, the application of different types of recycled aggregate concrete in different application scenarios still needs detailed research to better adapt to actual projects.
[0003] Water conservancy and hydropower projects have a huge demand for concrete. The aggregates used are all mined from the surrounding natural rivers or obtained by excavating stones from mountains. However, this mining method will cause very serious damage to the ecological environment. Therefore, the application of recycled aggregates in the field of hydraulic concrete has good ecological significance and economic value. At present, there are many studies on ordinary hydraulic concrete with recycled aggregates, and some of them have been successfully applied to physical projects. However, there are few studies on roller-compacted concrete, which is an important dam-building material in water conservancy and hydropower projects. Compared with ordinary concrete, roller-compacted concrete has the characteristics of less cementitious material, high proportion of aggregates, high content of stone powder in fine aggregates, and molding through vibration rolling.
[0004] Hydraulic structures are generally designed to have a long service life, and the service environment is exposed to water for a long time, so the requirements for concrete's anti-freeze-thaw damage and anti-permeability are high. Recycled aggregate hydraulic RCC has a much higher proportion of aggregate than ordinary recycled concrete, and the recycled aggregate itself has poor anti-freeze and anti-permeability. On the other hand, the fly ash content in hydraulic RCC is generally high, up to 40%~60%, and a high fly ash content will also have a certain adverse effect on the anti-freeze performance of concrete; at the same time, hydraulic RCC is a large volume concrete, which is very important for crack control. The recycled aggregate itself has a large porosity and poor thermal conductivity, so the concrete mixed with recycled aggregate generally has poor thermal conductivity. When the temperature difference between the inside and outside of the concrete is too large, temperature stress and temperature deformation will occur. If the tensile strength of the concrete is not enough to resist this stress, temperature cracks will occur. Therefore, the application of recycled aggregate in hydraulic RCC needs to solve the problem of poor anti-freeze, anti-permeability and thermal conductivity leading to difficult control of temperature cracks. Summary of the invention
[0005] The purpose of the present invention is to provide recycled aggregate hydraulic roller compacted concrete. By modifying recycled aggregate fine powder to replace part of the admixture, adding modified rubber powder and copper ore sand, and scientifically optimizing the concrete mix ratio, the various properties of the recycled aggregate hydraulic roller compacted concrete meet the design standard requirements, and the problem of poor frost resistance, poor impermeability and poor thermal conductivity of recycled aggregate in hydraulic roller compacted concrete is solved.
[0006] The second object of the present invention is to provide a method for preparing the above-mentioned recycled aggregate hydraulic rolled concrete.
[0007] The first technical solution adopted by the present invention is that the recycled aggregate hydraulic roller compacted concrete includes the following components, by weight: 120-130 parts of cement, 24-60 parts of fly ash, 60-104 parts of modified recycled micro powder, 25-30 parts of modified recycled rubber powder, 45-50 parts of 20-mesh copper ore sand, 40-45 parts of 80-mesh copper ore sand, 116-193 parts of ordinary large stone, 155-258 parts of ordinary medium stone, 116-193 parts of ordinary small stone, 193-270 parts of recycled large stone, 257-360 parts of recycled medium stone, 193-270 parts of recycled small stone, 190-316 parts of ordinary fine aggregate, 316-442 parts of recycled fine aggregate, 2.9-4.7 parts of water reducer, 0.19-0.34 parts of air entraining agent, 19-31 parts of alkali activator, and 120-130 parts of water.
[0008] The present invention is also characterized in that: The cement is ordinary Portland cement or medium-heat Portland cement. All performance indicators of ordinary Portland cement meet the requirements of GB 175-2023 "General Portland Cement", and all performance indicators of medium-heat Portland cement meet the requirements of GB / T 200-2017 "Medium-heat Portland Cement, Low-heat Portland Cement". The fly ash is Class F, Grade II fly ash, and all its performance indicators meet the requirements of GB / T 1596-2017 "Fly ash used in cement and concrete".
[0009] Modified recycled micro powder is obtained by modifying the original micro powder produced in the process of recycled aggregate production. Specifically, the original micro powder produced in the process of recycled aggregate production is ground by a planetary ball mill for 15 minutes or more to make the fineness of the recycled micro powder ≤25.0% and the activity index ≥70%; Modified recycled rubber powder is obtained by modifying recycled rubber powder with sodium hydroxide solution. The recycled rubber powder is made from waste tires and has an apparent density of 1020kg / m 3 , particle size is 60 mesh; Both 20-mesh copper ore sand and 80-mesh copper ore sand are sand-like copper ores obtained from copper mines after beneficiation. Their chemical components include iron oxide, silicon dioxide, aluminum oxide, calcium oxide, and cuprous oxide.
[0010] The particle size of ordinary large stone is 40~80mm, the particle size of ordinary medium stone is 20~40mm, the particle size of ordinary small stone is 5~20mm, the particle size of recycled large stone is 40~80mm, the particle size of recycled medium stone is 20~40mm, and the particle size of recycled small stone is 5~20mm; Ordinary large stones, ordinary medium stones and ordinary small stones are all made from natural parent rocks after crushing, and all performance indicators meet the requirements of "Specifications for Construction of Hydraulic Concrete" DL / T5144-2015; Recycled large stone, recycled medium stone and recycled small stone are all made from construction waste after cleaning, crushing and screening, and their apparent density is greater than 2350kg / m 3 , porosity less than 50%, water absorption less than 5.0%, crushing index less than 20%, firmness less than 10%, needle-like less than 10%, micropowder content less than 3.0%, sulfide and sulfate content less than 2.0%, and impurities less than 1.0%.
[0011] Ordinary fine aggregate is made from natural parent rock after crushing, and its performance indicators meet the requirements of "Specifications for Construction of Hydraulic Roller Compacted Concrete" DL / T5112-2021; Recycled fine aggregate is made from construction waste after cleaning, crushing and screening, and its apparent density is greater than 2350kg / m 3 , porosity less than 48%, bulk density less than 1300kg / m 3 , the maximum crushing index is less than 25%, the firmness is less than 10%, the fine powder content is less than 10%, the MB value is less than 1.4%, and the sulfide and sulfate content is less than 2.0%.
[0012] The water reducer is a high-efficiency naphthalene-based water reducer. The performance indicators of the water reducer and air entraining agent meet the requirements of the Technical Specification for Hydraulic Concrete Admixtures DL / T5100-2014; The alkaline activator is sodium silicate, and the chemical formula is Na2O·nSiO2.
[0013] The second technical solution adopted by the present invention is a method for preparing recycled aggregate hydraulic rolled concrete, and the specific steps are as follows: S1. Evenly mix the recycled large stone, the recycled medium stone and the recycled small stone with the ordinary large stone, the ordinary medium stone and the ordinary small stone respectively, add water to make the mixture reach a saturated surface dry state, and obtain a mixed coarse aggregate; S2, mixing ordinary fine aggregate, recycled fine aggregate, 20 mesh copper ore sand and 80 mesh copper ore sand evenly, adding water to make the mixture reach a saturated surface dry state, and obtaining mixed fine aggregate; S3, grinding the original micropowder produced in the process of recycled aggregate production to obtain modified recycled micropowder, and mixing cement, fly ash powder and modified recycled micropowder to obtain a cementitious material; S4, treating the regenerated rubber powder with a sodium hydroxide solution to obtain modified regenerated rubber powder; S5, adding sodium hydroxide to the alkali activator to reduce its modulus, and then adding the water reducer, air entraining agent and alkali activator into water and stirring evenly to form mixing water; S6, sequentially add the mixed coarse aggregate, the mixed fine aggregate, the modified recycled rubber powder, the cementitious material and the mixing water into a forced mixer for stirring for a time greater than or equal to 180 seconds to form a mixture; S7, rolling and molding the mixture to obtain recycled aggregate hydraulic rolled concrete.
[0014] The present invention is also characterized in that: The specific method of S4 is: soak the regenerated rubber powder in a 10% sodium hydroxide solution for 12 hours, then rinse with clean water and dry to obtain modified regenerated rubber powder.
[0015] The specific method of S5 is: take a sodium silicate solution with a modulus of 3.2 and a Baume degree of 40°Bé, and adjust the modulus to 1.5 by adding a 10% sodium hydroxide solution. The chemical reaction formula is as follows: Na2O·nSiO2+2NaOH→Na2O·nSiO2+Na2O+H2O.
[0016] The specific method of S7 is: forming according to the "Test Procedure for Hydraulic Roller Compacted Concrete" DL / T 5433-2024, curing to 90 days of age, and testing that the recycled aggregate hydraulic roller compacted concrete meets C 90 20W6F100 design requirements.
[0017] The beneficial effects of the present invention are: (1) Compared with ordinary concrete with recycled aggregate, the recycled aggregate hydraulic RCC proposed in the present invention has a higher proportion of aggregate and a higher content of particles below 0.16 mm and 0.08 mm in fine aggregate. The application of recycled aggregate in the field of hydraulic RCC can effectively utilize more construction waste; (2) The present invention uses a large amount of micro-powder produced in the production process of recycled aggregate. The micro-powder contains volcanic ash-active silicon and aluminum minerals and unhydrated cementitious material particles, which have a certain activity. The micro-powder is modified and then replaced with part of the admixture (replacement rate 50%-80%), so that the micro-powder that is a byproduct of the recycled aggregate is effectively utilized, further reducing the cost of concrete, realizing the reuse of micro-powder, and maximizing the environmental benefits; (3) The present invention uses recycled rubber powder produced from waste tires, which, after surface modification, replaces recycled fine aggregate in a certain proportion. On the basis of ensuring that the mechanical properties meet the requirements, the antifreeze and anti-seepage properties of recycled aggregate hydraulic roller compacted concrete are significantly improved, and the technical requirements of general dam construction roller compacted concrete can be met; (4) The present invention improves the thermal conductivity of recycled aggregate hydraulic roller compacted concrete by adding a certain proportion of copper ore sand to replace ordinary fine aggregate, effectively reducing temperature cracks; at the same time, it increases the unit density of concrete, which is more conducive to the volume design of the gravity dam. DETAILED DESCRIPTION
[0018] The present invention is described in detail below in conjunction with specific implementation modes.
[0019] The recycled aggregate hydraulic roller compacted concrete includes the following ingredients, measured by weight: 120-130 parts of cement, 24-60 parts of fly ash, 60-104 parts of modified recycled micropowder, 25-30 parts of modified recycled rubber powder, 45-50 parts of 20-mesh copper ore sand, 40-45 parts of 80-mesh copper ore sand, 116-193 parts of ordinary large stone, 155-258 parts of ordinary medium stone, 116-193 parts of ordinary small stone, 193-270 parts of recycled large stone, 257-360 parts of recycled medium stone, 193-270 parts of recycled small stone, 190-316 parts of ordinary fine aggregate, 316-442 parts of recycled fine aggregate, 2.9-4.7 parts of water reducer, 0.19-0.34 parts of air entraining agent, 19-31 parts of alkali activator, and 120-130 parts of water. By adopting a reasonable recycled aggregate replacement rate and scientific mix design, the performance indicators of recycled aggregate hydraulic RCC can meet the design requirements.
[0020] Among them, cement is ordinary Portland cement or medium-heat Portland cement. All performance indicators of ordinary Portland cement meet the requirements of "General Portland Cement" GB 175-2023, and all performance indicators of medium-heat Portland cement meet the requirements of "Medium-heat Portland Cement, Low-heat Portland Cement" GB / T 200-2017.
[0021] The fly ash is Class F, Grade II fly ash, and all its performance indicators meet the requirements of GB / T 1596-2017 "Fly ash used in cement and concrete".
[0022] Recycled micropowder is the original micropowder produced as a by-product in the production process of recycled aggregate. Recycled micropowder is construction waste with concrete and bricks as the main components. It is fly ash-like dust produced during the crushing, screening, shaping and other processes in the production of recycled aggregate. The general particle size is below 75um, and the chemical composition is SiO2, Al2O3, CaO, Fe2O3, etc. It has certain volcanic ash activity.
[0023] The modified recycled micropowder is obtained by modifying the original micropowder of the by-product produced in the production process of recycled aggregate. Specifically, the original micropowder of the by-product produced in the production process of recycled aggregate is ground by a planetary ball mill for 15 minutes or more, and the fineness of the modified recycled micropowder is ≤25.0% (45um square hole sieve residue), and the activity index is ≥70%.
[0024] A large amount of micropowder produced during the production of recycled aggregates contains volcanic ash-active silicon, aluminum minerals and unhydrated cementitious material particles, which have certain activity. The micropowder can be modified to replace part of the admixture, which can further reduce the cost of concrete while meeting the design standards, and make effective use of the micropowder that is a byproduct of recycled aggregates to maximize environmental benefits.
[0025] Modified recycled rubber powder is obtained by modifying recycled rubber powder with sodium hydroxide solution. The recycled rubber powder is made from waste tires and has an apparent density of 1020kg / m 3 The particle size is 60 mesh. After surface modification, the recycled rubber powder produced from waste tires replaces the recycled fine aggregate in a certain proportion, which significantly improves the antifreeze and anti-seepage properties of the recycled aggregate hydraulic RCC while ensuring that the mechanical properties meet the requirements.
[0026] 20 mesh copper ore sand and 80 mesh copper ore sand are both sandy copper ore obtained from copper ore after mining and beneficiation. Their chemical composition includes iron oxide, silicon dioxide, aluminum oxide, calcium oxide, and cuprous oxide, and they have good thermal conductivity. Adding a certain proportion of copper ore sand to replace ordinary fine aggregate can improve the thermal conductivity and unit density of recycled aggregate hydraulic roller compacted concrete while ensuring that the mechanical properties meet the requirements.
[0027] The particle size of ordinary large stone is 40~80mm, the particle size of ordinary medium stone is 20~40mm, and the particle size of ordinary small stone is 5~20mm. Ordinary large stone, ordinary medium stone and ordinary small stone are all made from natural parent rock after crushing. All performance indicators meet the requirements of "Specifications for Construction of Hydraulic Concrete" DL / T5144-2015.
[0028] The particle size of the recycled large stone is 40~80mm, the particle size of the recycled medium stone is 20~40mm, and the particle size of the recycled small stone is 5~20mm. The recycled large stone, recycled medium stone and recycled small stone are all made from construction waste after cleaning, crushing and screening. The apparent density is greater than 2350kg / m 3 , porosity less than 50%, water absorption less than 5.0%, crushing index less than 20%, firmness less than 10%, needle-like less than 10%, micropowder content less than 3.0%, sulfide and sulfate content less than 2.0%, and impurities less than 1.0%.
[0029] Ordinary fine aggregate is made from crushed natural parent rock, and its performance indicators all meet the requirements of "Specifications for Construction of Hydraulic Roller Compacted Concrete" DL / T5112-2021.
[0030] Recycled fine aggregate is made from construction waste after cleaning, crushing and screening, and its apparent density is greater than 2350kg / m 3 , porosity less than 48%, bulk density less than 1300kg / m 3 , the maximum crushing index is less than 25%, the firmness is less than 10%, the fine powder content is less than 10%, the MB value is less than 1.4%, and the sulfide and sulfate content is less than 2.0%.
[0031] The water reducer is a high-efficiency naphthalene-based water reducer. The performance indicators of the water reducer and air entraining agent meet the requirements of "Technical Specifications for Hydraulic Concrete Admixtures" DL / T5100-2014.
[0032] The alkaline activator is sodium silicate, and the chemical formula is Na2O·nSiO2.
[0033] The preparation method of the recycled aggregate hydraulic rolled concrete comprises the following specific steps: S1. Evenly mix the recycled large stone, the recycled medium stone and the recycled small stone with the ordinary large stone, the ordinary medium stone and the ordinary small stone respectively, add water to make the mixture reach a saturated surface dry state, and obtain a mixed coarse aggregate; S2, mixing ordinary fine aggregate, recycled fine aggregate, 20 mesh copper ore sand and 80 mesh copper ore sand evenly, adding water to make the mixture reach a saturated surface dry state, and obtaining mixed fine aggregate; S3, grinding the original micropowder produced in the process of recycled aggregate production to obtain modified recycled micropowder, which is used to stimulate the activity of the micropowder. The recycled micropowder is ground to expose the surface of the unhydrated cement particles that are wrapped, and at the same time increase the specific surface area and improve its activity; Then cement, fly ash powder and modified recycled micro powder are mixed to obtain a cementitious material; S4. Treat the regenerated rubber powder with a sodium hydroxide solution to obtain modified regenerated rubber powder; the specific method is: soak the regenerated rubber powder in a 10% sodium hydroxide solution for 12 hours, then rinse with water and dry to obtain modified regenerated rubber powder. The purpose is to increase the surface roughness of the rubber particles and deeply clean the surface of the rubber particles, so as to reduce its hydrophobicity and improve the bonding performance of cement slurry.
[0034] S5, adding sodium hydroxide to the alkali activator to reduce its modulus, and then adding the water reducer, air entraining agent and alkali activator into water and stirring evenly to form mixing water; The specific method for reducing the modulus of the alkali activator is: taking a sodium silicate solution with a modulus of 3.2 and a Baume degree of 40°Bé, and adjusting the modulus to 1.5 by adding a 10% sodium hydroxide solution, the chemical reaction formula is as follows: Na2O·nSiO2+2NaOH→Na2O·nSiO2+Na2O+H2O.
[0035] The purpose of adding sodium silicate alkali activator in this step is to further stimulate the activity of micro powder and fly ash.
[0036] S6, sequentially add the mixed coarse aggregate, the mixed fine aggregate, the modified recycled rubber powder, the cementitious material and the mixing water into a forced mixer for stirring for a time greater than or equal to 180 seconds to form a mixture; S7, rolling and molding the mixture to obtain recycled aggregate hydraulic rolled concrete, the specific method is: molding according to the "Testing Procedure for Hydraulic Rolled Concrete" DL / T 5433-2024, curing to 90 days of age, and testing that the recycled aggregate hydraulic rolled concrete meets C 90 20W6F100 design requirements.
[0037] The main principle of the present invention is to improve the antifreeze and anti-permeability properties of recycled aggregate hydraulic roller compacted concrete by adding a certain proportion of modified rubber powder to replace fine aggregate of the same particle size (0.3mm). Since rubber powder is a hydrophobic polymer material, it can form a hydrophobic film on the surface, increase the seepage resistance of water, reduce the suction force of capillary pores, and thus reduce the anti-permeability of concrete; in the dynamic thawing cycle, liquid water and solid water are transformed into each other, and the volume changes accordingly to produce frost heave stress, and rubber particles have high elastic properties, which can effectively absorb this part of the stress, thereby enhancing the antifreeze performance of roller compacted concrete; By adding a certain proportion of copper ore sand to replace ordinary fine aggregates with the same particle size (1.18mm, 0.16mm), the thermal conductivity of concrete can be enhanced, thereby effectively reducing temperature cracks. On the other hand, for gravity dams, the addition of copper ore sand can also increase the unit density of concrete, which is beneficial to the volume design of the dam body; the thermal conductivity of copper ore sand is higher than that of ordinary rock aggregates, and the bulk density is greater than that of ordinary rock aggregates, so the addition of copper ore sand can improve the thermal conductivity of concrete and increase the bulk density; The activity of the recycled micropowder is significantly improved through mechanical ball milling and alkali activation, so that it can replace the traditional admixture fly ash in a high proportion; the unhydrated cement particles wrapped in the recycled micropowder are exposed to the surface again through grinding, and the specific surface area is increased to improve its activity; The mechanism of using sodium silicate to stimulate the activity of regenerated micropowder is mainly reflected in that the NaOH produced after the hydration of sodium silicate acts on the glass in the micropowder to hydrate and decompose it, and reorganize it to generate new CASH gel and CSH gel, thereby improving the density of concrete.
[0038] Compared with ordinary concrete with recycled aggregate, the recycled aggregate hydraulic roller compacted concrete prepared by the present invention has a higher utilization rate of recycled aggregate. Because a large number of particles below 0.16 mm and 0.08 mm are generated during the production process of recycled aggregate, most of these particles are discarded when used in ordinary concrete, while there is a lower limit requirement for these tiny particles in the recycled aggregate hydraulic roller compacted concrete, so the content is higher, so the recycled aggregate hydraulic roller compacted concrete can consume more construction waste and improve its utilization rate.
[0039] The carbonization problem of recycled concrete has always been one of the important factors restricting its development and promotion. The carbonization damage of concrete mainly comes from the loss of protection of steel bars by concrete after carbonization, which causes steel bars to rust and expand, and then destroys the concrete structure. The hydraulic roller compacted concrete used in the present invention generally has less or no steel bars, so it is less affected by carbonization. On the other hand, the carbonate generated by the carbonization reaction can also fill the pores in the recycled concrete, which can improve the surface strength and durability of the recycled aggregate hydraulic roller compacted concrete to a certain extent. Therefore, recycled aggregate has better applicability for hydraulic roller compacted concrete.
[0040] The invention can provide a technical reference for the application of recycled aggregate in roller compacted concrete of dam bodies of water conservancy and hydropower projects.
[0041] Example 1 Recycled aggregate hydraulic roller compacted concrete includes the following ingredients, by weight: 120 parts of cement, 48 parts of fly ash, 72 parts of modified recycled micropowder, 26 parts of modified recycled rubber powder, 45 parts of 20 mesh copper ore sand, 40 parts of 80 mesh copper ore sand, 193 parts of ordinary large stone, 258 parts of ordinary medium stone, 193 parts of ordinary small stone, 193 parts of recycled large stone, 258 parts of recycled medium stone, 193 parts of recycled small stone, 316 parts of ordinary fine aggregate, 316 parts of recycled fine aggregate, 3.0 parts of water reducer, 0.19 parts of air entraining agent, 19 parts of alkali activator, and 120 parts of water.
[0042] Among them, the cement is ordinary Portland cement, and all performance indicators of ordinary Portland cement meet the requirements of "General Portland Cement" GB 175-2023.
[0043] The fly ash is Class F, Grade II fly ash, and all its performance indicators meet the requirements of GB / T 1596-2017 "Fly ash used in cement and concrete".
[0044] The modified recycled micropowder is obtained by modifying the original micropowder of the by-product produced in the production process of recycled aggregate. Specifically, the original micropowder of the by-product produced in the production process of recycled aggregate is ground by a planetary ball mill for 18 minutes, and the fineness of the modified recycled micropowder is ≤25.0%, and the residue is sieved with a 45um square hole sieve, and the activity index is ≥70%.
[0045] Modified recycled rubber powder is obtained by modifying recycled rubber powder with sodium hydroxide solution. The recycled rubber powder is made from waste tires and has an apparent density of 1020kg / m 3 , particle size is 60 mesh.
[0046] Both 20-mesh copper ore sand and 80-mesh copper ore sand are sand-like copper ore obtained from copper mines after beneficiation. Their chemical composition includes iron oxide, silicon dioxide, aluminum oxide, calcium oxide, and cuprous oxide, and they have good thermal conductivity.
[0047] The particle size of ordinary large stone is 40~80mm, the particle size of ordinary medium stone is 20~40mm, and the particle size of ordinary small stone is 5~20mm. Ordinary large stone, ordinary medium stone and ordinary small stone are all made from natural parent rock after crushing. All performance indicators meet the requirements of "Specifications for Construction of Hydraulic Concrete" DL / T5144-2015.
[0048] The particle size of the recycled large stone is 40~80mm, the particle size of the recycled medium stone is 20~40mm, and the particle size of the recycled small stone is 5~20mm. The recycled large stone, recycled medium stone and recycled small stone are all made from construction waste after cleaning, crushing and screening. The apparent density is greater than 2350kg / m 3 , porosity less than 50%, water absorption less than 5.0%, crushing index less than 20%, firmness less than 10%, needle-like less than 10%, micropowder content less than 3.0%, sulfide and sulfate content less than 2.0%, and impurities less than 1.0%.
[0049] Ordinary fine aggregate is made from crushed natural parent rock, and its performance indicators all meet the requirements of "Specifications for Construction of Hydraulic Roller Compacted Concrete" DL / T5112-2021.
[0050] Recycled fine aggregate is made from construction waste after cleaning, crushing and screening, and its apparent density is greater than 2350kg / m 3 , porosity less than 48%, bulk density less than 1300kg / m 3 , the maximum crushing index is less than 25%, the firmness is less than 10%, the fine powder content is less than 10%, the MB value is less than 1.4%, and the sulfide and sulfate content is less than 2.0%.
[0051] The water reducer is a high-efficiency naphthalene-based water reducer. The performance indicators of the water reducer and air entraining agent meet the requirements of "Technical Specifications for Hydraulic Concrete Admixtures" DL / T5100-2014.
[0052] The alkaline activator is sodium silicate, and the chemical formula is Na2O·nSiO2.
[0053] The preparation method of the recycled aggregate hydraulic rolled concrete comprises the following specific steps: S1. Evenly mix the recycled large stone, the recycled medium stone and the recycled small stone with the ordinary large stone, the ordinary medium stone and the ordinary small stone respectively, add water to make the mixture reach a saturated surface dry state, and obtain a mixed coarse aggregate; S2, mixing ordinary fine aggregate, recycled fine aggregate, 20 mesh copper ore sand and 80 mesh copper ore sand evenly, adding water to make the mixture reach a saturated surface dry state, and obtaining mixed fine aggregate; S3, grinding the original micropowder of the by-product generated in the production process of recycled aggregate to obtain modified recycled micropowder; then mixing cement, fly ash powder and the modified recycled micropowder to obtain a cementitious material; S4, soaking the regenerated rubber powder in a 10% sodium hydroxide solution for 12 hours, then washing with clean water and drying to obtain modified regenerated rubber powder; S5. Take a sodium silicate solution with a modulus of 3.2 and a Baume degree of 40°Bé, and adjust the modulus to 1.5 by adding a 10% sodium hydroxide solution. The chemical reaction formula is as follows: Na2O·nSiO2+2NaOH→Na2O·nSiO2+Na2O+H2O.
[0054] Then add water reducing agent, air entraining agent and alkali activator into water and stir evenly to form mixing water; S6, sequentially add the mixed coarse aggregate, mixed fine aggregate, modified recycled rubber powder, cementitious material and mixing water into a forced mixer for 180 seconds to form a mixture; S7. The mixture was rolled and formed according to the "Test Procedure for Hydraulic Roller Compacted Concrete" DL / T 5433-2024, and cured to 90 days of age. The various properties of the recycled aggregate hydraulic roller compacted concrete were tested and compared with the various properties of ordinary aggregate hydraulic roller compacted concrete of the same design grade. The performance comparison results are shown in Table 1 below.
[0055] Table 1 Comparison of recycled aggregate hydraulic RCC and common aggregate hydraulic RCC in Example 1
[0056] Example 2 Recycled aggregate hydraulic roller compacted concrete includes the following ingredients, by weight: 125 parts of cement, 50 parts of fly ash, 75 parts of modified recycled micropowder, 28 parts of modified recycled rubber powder, 48 parts of 20 mesh copper ore sand, 43 parts of 80 mesh copper ore sand, 193 parts of ordinary large stone, 258 parts of ordinary medium stone, 193 parts of ordinary small stone, 193 parts of recycled large stone, 258 parts of recycled medium stone, 193 parts of recycled small stone, 316 parts of ordinary fine aggregate, 316 parts of recycled fine aggregate, 3.2 parts of water reducer, 0.25 parts of air entraining agent, 25 parts of alkali activator and 125 parts of water.
[0057] Among them, the cement is medium-heat Portland cement, and all performance indicators of medium-heat Portland cement meet the requirements of "Medium-heat Portland Cement, Low-heat Portland Cement" GB / T 200-2017.
[0058] The specifications and preparation methods of fly ash, modified recycled micropowder, modified recycled rubber powder, 20-mesh copper ore sand and 80-mesh copper ore sand are the same as those in Example 1.
[0059] The particle size specifications of ordinary large stone, ordinary medium stone, ordinary small stone, recycled large stone, recycled medium stone and recycled small stone are all the same as those in Example 1.
[0060] The specific steps of the preparation method of the recycled aggregate hydraulic rolled concrete are the same as those of Example 1.
[0061] The mixture was rolled and formed according to the "Test Procedure for Hydraulic Roller Compacted Concrete" DL / T 5433-2024 and cured to 90 days of age. The various properties of the recycled aggregate hydraulic roller compacted concrete were tested and compared with the various properties of ordinary aggregate hydraulic roller compacted concrete of the same design grade. The performance comparison results are shown in Table 2 below.
[0062] Table 2 Comparison of recycled aggregate hydraulic RCC and common aggregate hydraulic RCC in Example 2
[0063] Example 3 Recycled aggregate hydraulic roller compacted concrete includes the following ingredients, by weight: 130 parts of cement, 26 parts of fly ash, 104 parts of modified recycled micropowder, 30 parts of modified recycled rubber powder, 50 parts of 20 mesh copper ore sand, 45 parts of 80 mesh copper ore sand, 193 parts of ordinary large stone, 258 parts of ordinary medium stone, 193 parts of ordinary small stone, 193 parts of recycled large stone, 258 parts of recycled medium stone, 193 parts of recycled small stone, 316 parts of ordinary fine aggregate, 316 parts of recycled fine aggregate, 4.4 parts of water reducer, 0.34 parts of air entraining agent, 31 parts of alkali activator and 130 parts of water.
[0064] Among them, the cement is medium-heat Portland cement, and all performance indicators of medium-heat Portland cement meet the requirements of "Medium-heat Portland Cement, Low-heat Portland Cement" GB / T 200-2017.
[0065] The specifications and preparation methods of fly ash, modified recycled micropowder, modified recycled rubber powder, 20-mesh copper ore sand and 80-mesh copper ore sand are the same as those in Example 1.
[0066] The particle size specifications of ordinary large stone, ordinary medium stone, ordinary small stone, recycled large stone, recycled medium stone and recycled small stone are all the same as those in Example 1.
[0067] The specific steps of the preparation method of the recycled aggregate hydraulic rolled concrete are the same as those of Example 1.
[0068] The mixture was rolled and formed according to the "Test Procedure for Hydraulic Roller Compacted Concrete" DL / T 5433-2024, cured to 90 days of age, and compared with the performance of ordinary aggregate hydraulic roller compacted concrete of the same design grade. The performance comparison results are shown in Table 3 below.
[0069] Table 3 Comparison between recycled aggregate hydraulic RCC and ordinary aggregate hydraulic RCC in Example 3
[0070] Example 4 The recycled aggregate hydraulic roller compacted concrete includes the following ingredients, by weight: 125 parts of cement, 50 parts of fly ash, 60 parts of modified recycled micropowder, 28 parts of modified recycled rubber powder, 48 parts of 20 mesh copper ore sand, 43 parts of 80 mesh copper ore sand, 153 parts of ordinary large stone, 204 parts of ordinary medium stone, 153 parts of ordinary small stone, 229 parts of recycled large stone, 305 parts of recycled medium stone, 229 parts of recycled small stone, 250 parts of ordinary fine aggregate, 374 parts of recycled fine aggregate, 4.5 parts of water reducer, 0.30 parts of air entraining agent, 25 parts of alkali activator and 125 parts of water.
[0071] Among them, the specifications and preparation methods of cement, fly ash, modified recycled micropowder, modified recycled rubber powder, 20-mesh copper ore sand and 80-mesh copper ore sand are the same as those in Example 1.
[0072] The particle size specifications of ordinary large stone, ordinary medium stone, ordinary small stone, recycled large stone, recycled medium stone and recycled small stone are all the same as those in Example 1.
[0073] The specific steps of the preparation method of the recycled aggregate hydraulic rolled concrete are the same as those of Example 1.
[0074] The mixture was rolled and formed according to the "Test Procedure for Hydraulic Roller Compacted Concrete" DL / T 5433-2024 and cured to 90 days. The various properties of the recycled aggregate hydraulic roller compacted concrete were tested and compared with the various properties of ordinary aggregate hydraulic roller compacted concrete of the same design grade. The performance comparison results are shown in Table 4 below.
[0075] Table 4 Comparison of recycled aggregate hydraulic RCC and common aggregate hydraulic RCC in Example 4
[0076] Example 5 The recycled aggregate hydraulic roller compacted concrete includes the following ingredients, by weight: 125 parts of cement, 50 parts of fly ash, 75 parts of modified recycled micropowder, 28 parts of modified recycled rubber powder, 48 parts of 20 mesh copper ore sand, 43 parts of 80 mesh copper ore sand, 116 parts of ordinary large stone, 155 parts of ordinary medium stone, 116 parts of ordinary small stone, 267 parts of recycled large stone, 356 parts of recycled medium stone, 267 parts of recycled small stone, 190 parts of ordinary fine aggregate, 437 parts of recycled fine aggregate, 4.7 parts of water reducer, 0.34 parts of air entraining agent, 25 parts of alkali activator and 125 parts of water.
[0077] Among them, the specifications and preparation methods of cement, fly ash, modified recycled micropowder, modified recycled rubber powder, 20-mesh copper ore sand and 80-mesh copper ore sand are the same as those in Example 1.
[0078] The particle size specifications of ordinary large stone, ordinary medium stone, ordinary small stone, recycled large stone, recycled medium stone and recycled small stone are all the same as those in Example 1.
[0079] The specific steps of the preparation method of the recycled aggregate hydraulic rolled concrete are the same as those of Example 1.
[0080] The mixture was rolled and formed according to the "Test Procedure for Hydraulic Roller Compacted Concrete" DL / T 5433-2024 and cured to 90 days of age. The various properties of the recycled aggregate hydraulic roller compacted concrete were tested and compared with the various properties of ordinary aggregate hydraulic roller compacted concrete of the same design grade. The performance comparison results are shown in Table 5 below.
[0081] Table 5 Comparison of recycled aggregate hydraulic RCC and common aggregate hydraulic RCC in Example 5
[0082] Example 6 The recycled aggregate hydraulic roller compacted concrete includes the following ingredients, by weight: 120 parts of cement, 24 parts of fly ash, 96 parts of modified recycled micropowder, 26 parts of modified recycled rubber powder, 50 parts of 20 mesh copper ore sand, 45 parts of 80 mesh copper ore sand, 154 parts of ordinary large stone, 206 parts of ordinary medium stone, 154 parts of ordinary small stone, 232 parts of recycled large stone, 309 parts of recycled medium stone, 232 parts of recycled small stone, 252 parts of ordinary fine aggregate, 379 parts of recycled fine aggregate, 4.6 parts of water reducer, 0.29 parts of air entraining agent, 29 parts of alkali activator and 120 parts of water.
[0083] Among them, the particle size specifications of cement, fly ash, modified recycled micropowder, modified recycled rubber powder, 20 mesh copper ore sand and 80 mesh copper ore sand, ordinary large stone, ordinary medium stone, ordinary small stone, recycled large stone, recycled medium stone and recycled small stone are the same as those in Example 1.
[0084] The specific steps of the preparation method of the recycled aggregate hydraulic rolled concrete are the same as those of Example 1.
[0085] The mixture was rolled and formed according to the "Test Procedure for Hydraulic Roller Compacted Concrete" DL / T 5433-2024 and cured to 90 days. The various properties of the recycled aggregate hydraulic roller compacted concrete were tested and compared with the various properties of ordinary aggregate hydraulic roller compacted concrete of the same design grade. The performance comparison results are shown in Table 6 below.
[0086] Table 6 Comparison of recycled aggregate hydraulic RCC and common aggregate hydraulic RCC in Example 6
[0087] It can be seen from Tables 1-6 that compared with ordinary aggregate hydraulic RCC of the same design grade, the mechanical properties, frost resistance, impermeability, thermal conductivity and apparent density of the recycled aggregate hydraulic RCC prepared by the preparation method of the present invention are reduced to a certain extent, and the linear expansion coefficient is slightly increased. 90 In terms of the design grade of 20W6F100, recycled aggregate hydraulic RCC can still meet the design requirements, while in the field of hydraulic dam RCC, most of the design grades are lower than C 90 20W6F100, so from the perspective of concrete performance, environmental benefits and economy, recycled aggregate can be used in hydraulic RCC.
Claims
1. Recycled aggregate hydraulic rolled concrete, characterized in that: The invention comprises the following ingredients in parts by weight: 120-130 parts of cement, 24-60 parts of fly ash, 60-104 parts of modified recycled micro powder, 25-30 parts of modified recycled rubber powder, 45-50 parts of 20-mesh copper ore sand, 40-45 parts of 80-mesh copper ore sand, 116-193 parts of ordinary large stone, 155-258 parts of ordinary medium stone, 116-193 parts of ordinary small stone, 193-270 parts of recycled large stone, 257-360 parts of recycled medium stone, 193-270 parts of recycled small stone, 190-316 parts of ordinary fine aggregate, 316-442 parts of recycled fine aggregate, 2.9-4.7 parts of water reducer, 0.19-0.34 parts of air entraining agent, 19-31 parts of alkali activator and 120-130 parts of water.
2. The recycled aggregate hydraulic rolled concrete according to claim 1, characterized in that: The cement is ordinary Portland cement or medium-heat Portland cement, and the performance indicators of the ordinary Portland cement meet the requirements of the "General Portland Cement" GB175-2023 specification, and the performance indicators of the medium-heat Portland cement meet the requirements of the "Medium-heat Portland Cement, Low-heat Portland Cement" GB / T 200-2017 specification; The fly ash is Class F Grade II fly ash, and all performance indicators thereof meet the requirements of the specification GB / T 1596-2017 "Fly ash used in cement and concrete".
3. The recycled aggregate hydraulic rolled concrete according to claim 1, characterized in that: The modified regenerated micropowder is obtained by modifying the original micropowder of the by-product produced in the production process of the regenerated aggregate. Specifically, the original micropowder of the by-product produced in the production process of the regenerated aggregate is ground by a planetary ball mill for 15 minutes or more, so that the fineness of the regenerated micropowder is ≤25.0% and the activity index is ≥70%; The modified regenerated rubber powder is obtained by modifying the regenerated rubber powder with a sodium hydroxide solution. The regenerated rubber powder is made from waste tires and has an apparent density of 1020 kg / m 3 , particle size is 60 mesh; The 20-mesh copper ore sand and the 80-mesh copper ore sand are both sandy copper ores obtained from copper mines after beneficiation, and their chemical components include iron oxide, silicon dioxide, aluminum oxide, calcium oxide, and cuprous oxide.
4. The recycled aggregate hydraulic rolled concrete according to claim 1, characterized in that: The particle size of the ordinary large stone is 40-80 mm, the particle size of the ordinary medium stone is 20-40 mm, the particle size of the ordinary small stone is 5-20 mm, the particle size of the recycled large stone is 40-80 mm, the particle size of the recycled medium stone is 20-40 mm, and the particle size of the recycled small stone is 5-20 mm; The ordinary large stone, ordinary medium stone and ordinary small stone are all made from natural parent rocks after crushing, and all performance indicators meet the requirements of "Specification for Construction of Hydraulic Concrete" DL / T5144-2015; The regenerated large stone, regenerated medium stone and regenerated small stone are all made from construction waste after cleaning, crushing and screening, and their apparent density is greater than 2350kg / m 3 , porosity less than 50%, water absorption less than 5.0%, crushing index less than 20%, firmness less than 10%, needle-like less than 10%, micropowder content less than 3.0%, sulfide and sulfate content less than 2.0%, and impurities less than 1.0%.
5. The recycled aggregate hydraulic rolled concrete according to claim 1, characterized in that: The ordinary fine aggregate is made from natural parent rock after crushing, and its various performance indicators meet the requirements of "Construction Specification for Hydraulic Roller Compacted Concrete" DL / T5112-2021; The recycled fine aggregate is made from construction waste after cleaning, crushing and screening, and its apparent density is greater than 2350kg / m 3 , porosity less than 48%, bulk density less than 1300kg / m 3 , the maximum crushing index is less than 25%, the firmness is less than 10%, the fine powder content is less than 10%, the MB value is less than 1.4%, and the sulfide and sulfate content is less than 2.0%.
6. The recycled aggregate hydraulic rolled concrete according to claim 1, characterized in that: The water reducer is a high-efficiency naphthalene-based water reducer, and the performance indicators of the water reducer and air entraining agent meet the requirements of "Technical Specifications for Hydraulic Concrete Admixtures" DL / T5100-2014; The alkaline activator is sodium silicate, and the chemical formula is Na2O·nSiO2.
7. The method for preparing recycled aggregate hydraulic rolled concrete according to any one of claims 1 to 6, characterized in that: The specific steps are as follows: S1. Evenly mix the recycled large stone, the recycled medium stone and the recycled small stone with the ordinary large stone, the ordinary medium stone and the ordinary small stone respectively, add water to make the mixture reach a saturated surface dry state, and obtain a mixed coarse aggregate; S2, mixing ordinary fine aggregate, recycled fine aggregate, 20 mesh copper ore sand and 80 mesh copper ore sand evenly, adding water to make the mixture reach a saturated surface dry state, and obtaining mixed fine aggregate; S3, grinding the original micropowder produced in the process of recycled aggregate production to obtain modified recycled micropowder, and mixing cement, fly ash powder and modified recycled micropowder to obtain a cementitious material; S4, treating the regenerated rubber powder with a sodium hydroxide solution to obtain modified regenerated rubber powder; S5, adding sodium hydroxide to the alkali activator to reduce its modulus, and then adding the water reducer, air entraining agent and alkali activator into water and stirring evenly to form mixing water; S6, sequentially add the mixed coarse aggregate, the mixed fine aggregate, the modified recycled rubber powder, the cementitious material and the mixing water into a forced mixer for stirring for a time greater than or equal to 180 seconds to form a mixture; S7, rolling and molding the mixture to obtain recycled aggregate hydraulic rolled concrete.
8. The method for preparing recycled aggregate hydraulic rolled concrete according to claim 7, characterized in that: The specific method of S4 is: soaking the regenerated rubber powder in a 10% sodium hydroxide solution for 12 hours, then washing with clean water and drying to obtain modified regenerated rubber powder.
9. The method for preparing recycled aggregate hydraulic rolled concrete according to claim 7, characterized in that: The specific method of S5 is: taking a sodium silicate solution with a modulus of 3.2 and a Baume degree of 40°Bé, and adjusting the modulus to 1.5 by adding a 10% sodium hydroxide solution, the chemical reaction formula is as follows: Na2O·nSiO2+2NaOH→Na2O·nSiO2+Na2O+H2O.
10. The method for preparing recycled aggregate hydraulic rolled concrete according to claim 7, characterized in that: The specific method of S7 is: forming and curing to 90 days according to the "Test Procedure for Hydraulic Roller Compacted Concrete" DL / T 5433-2024, and the recycled aggregate hydraulic roller compacted concrete meets the C 90 20W6F100 design requirements.
Citation Information
Patent Citations
Cement-enveloped sand roller compacted concrete and preparation process thereof
CN110255994A
Fiber-reinforced carborundum wear-resistant ground construction method
CN111848069A
Composite activated regenerated micro-powder concrete based on slurry coating process and preparation method of composite activated regenerated micro-powder concrete
CN115124317A
Roller compacted concrete prepared from solid waste material and application of roller compacted concrete
CN117466604A
Modified fly ash-containing concrete for pavement
JP2015151318A